Traditional Ayurvedic and herbal remedies for Alzheimer's disease: from bench to bedside - Sharma, Rohit; Kuca, Kamil; Nepovimova, Eugenie; Kabra, Atul; Rao, M M; Prajapati, P K (Expert review of neurotherapeutics, 2019)
Alzheimer's disease (AD) is a progressive, neurodegenerative disorder prevalent worldwide among elderly populations. Owing to limited efficacy, side effects, and poor patient compliance for current rationally designed therapies, options are being searched from alternate therapies such as Indian (Ayurvedic), Chinese, or other traditional systems. Areas covered: Following a comprehensive literature search, the authors provide a review encompassing: (1) pathophysiological changes involved in AD, (2) Ayurvedic holistic approach and herbal medicines to manage dementia and AD, and (3) traditional plants and their phytoconstituents effective in AD with description of possible mechanism of action. Expert opinion: Traditional remedies could be adjunct therapeutic options to allay wide-ranging pathological cascades of AD. Ayurveda offers a holistic approach of treatment along with a list of nootropic herbs and formulations that are the rich sources of antioxidants, anti-amyloidogenic, neuroprotective, adaptogenic, anti-inflammatory, and immunomodulatory compounds that are found to modulate neuroendocrine-immune activities, enhance memory, intellect, rejuvenate brain functions, and improve quality of life. A strong knowledge base of traditional systems coupled with contemporary science may provide new functional leads for age-associated neurodegenerative disorders at preventive, promotive, and curative levels, and evolution of new drug therapies and development processes, though further research is needed.
Keywords: herbal medicine; amyloid beta; Alzheimerova nemoc; dementia; Ayurveda; lidé; acetylcholinesterase; neurodegenerative disease; fytoterapie; Alzheimer’s disease; Phytotherapy; traditional medicine; Alzheimer Disease; neurofibrillary tangles; Medicine, Ayurvedic; ájurvéda; Humans